Elevated phospholipase D activity in androgen-insensitive prostate cancer cells promotes both survival and metastatic phenotypes. (1st June 2018) - Utter, Matthew; Chakraborty, Sohag; Goren, Limor; Feuser, Lucas; Zhu, Yuan-Shan; Foster, David A.
Abstract: Prostate cells are hormonally driven to grow and divide. Typical treatments for prostate cancer involve blocking activation of the androgen receptor by androgens. Androgen deprivation therapy can lead to the selection of cancer cells that grow and divide independently of androgen receptor activation. Prostate cancer cells that are insensitive to androgens commonly display metastatic phenotypes and reduced long-term survival of patients. In this study we provide evidence that androgen-insensitive prostate cancer cells have elevated PLD activity relative to the androgen-sensitive prostate cancer cells. PLD activity has been linked with promoting survival in many human cancer cell lines; and consistent with the previous studies, suppression of PLD activity in the prostate cancer cells resulted in apoptotic cell death. Of significance, suppressing the elevated PLD activity in androgen resistant prostate cancer lines also blocked the ability of these cells to migrate and invade Matrigel™. Since survival signals are generally an early event in tumorigenesis, the apparent coupling of survival and metastatic phenotypes implies that metastasis is an earlier event in malignant prostate cancer than generally thought. This finding has implications for screening strategies designed to identify prostate cancers before dissemination. Highlights: The first line of defense against cancer is suppression of default apoptotic programs. Signals that suppress apoptosis are known as survival signals and occur early in tumorigenesis. Elevated phospholipase D activity and phosphatidic acid production promotes an mTOR-dependent survival signal. Phospholipase D promotes both survival and metastatic phenotypes in androgen-independent prostate cancer cells. The implication is that metastasis is an earlier event in prostate cancer than generally appreciated..